International trade and its impact on the national economy - Yuldoshev Elbek Sobir ugli (THE INNOVATION ECONOMY, 2026)
This article discusses the essence, forms, and positive and negative impacts of international trade on the national economy. International trade creates the basis for expanding economic relations between countries, increasing competitiveness, and introducing innovations and technologies. The article also analyzes the modern directions of international trade policy, export-import structure, and its contribution to economic development using the example of Uzbekistan. Conclusions and proposals based on the results serve to improve national economic strategies.